The Canadian CASSIOPE small satellite mission: The enhanced polar outflow probe and Cascade technology demonstration payloads. (May 2015) - Yau, A.W.; Ali, Z.; Alonso, C.; Casgrain, C.; Enno, G.A.; Entus, B.; Grigorian, M.; Hemingway, J.; Howarth, A.; Hum, R.H.; James, H.G.; Langlois, P.; et al.
Abstract: We present the initial scientific results from the CASSIOPE small satellite mission, which was successfully launched on September 29, 2013 into an elliptic polar orbit of 325×1500 km at 81° inclination. The CASSIOPE spacecraft uses the Canadian small satellite bus to carry the Enhanced Polar Outflow Probe (e-POP) scientific (space weather research) payload and the Cascade communications technology demonstration payload into orbit. The e-POP payload is comprised of a suite of eight high-resolution plasma, magnetic field, radio, and optical instruments designed for in-situ observations in the topside polar ionosphere at the highest-possible resolution. The payload utilizes the advanced data storage and telemetry downlink capability of Cascade to meet its large data downlink bandwidth requirements – and to help demonstrate the capabilities of Cascade in the process. We present preliminary results from the first several months of CASSIOPE mission operation, to demonstrate the performance of both payloads, and the scientific capabilities of the e-POP mission in coordination with other observing facilities. Highlights: CASSIOPE successfully launched in September 2013 into elliptic polar orbit. Multi-purpose "hybrid" satellite carries two payloads: e-POP and Cascade. e-POP carries 8 high-resolution plasma, field, radio, and optical instruments. Preliminary results from early CASSIOPE mission operation are presented.